Minimally invasive renal autotransplantation. Issue 7 (20th May 2015) - Sood, Akshay; Jeong, Wooju; Ahlawat, Rajesh; Abdollah, Firas; Sammon, Jesse D.; Bhandari, Mahendra; Menon, Mani
Abstract : Minimally invasive renal allotransplantation techniques have been recently described; reported benefits include reduced morbidity/complications. These benefits have been successfully adapted for minimally invasive renal autotransplantation, however, in a non‐oncological setting. We, here, describe a novel alternative robot‐assisted renal autotransplantation technique, utilizing GelPOINT, which by permitting ex vivo graft examination and surgery might allow further broadening of indications for minimally‐invasive renal autotransplantation, to include complex oncological renal/ureteral lesions. Future studies are needed to evaluate the utility of these techniques. J. Surg. Oncol. 2015;112:717–722 . © 2015 Wiley Periodicals, Inc.